Role of Maternal & Fetal Factors in Relation to Low Birth Weight - Islam, Tasnuva; Mahboob, Abdullah Al; Ahammad, Forrukh (Medicine Today, 2022)
Introduction: Low birth weight (LBW) continues to remain a major public health problem worldwide. There are numerous factors contributing to LBW both maternal and fetal. The mortality of low birth weight can be reduced if the risk factors are detected early and managed by simple techniques. Objective: To identify the maternal and fetal factors associated with low birth weight. Materials and Methods: This case control study was conducted in Department of Pediatrics, Khulna Medical College& Hospital from January 2019 to June 2019. After delivery of the baby weight of the newborn was measured with digital weighing scale. Mothers of babies with birth weight <2500 gm were enrolled as cases and mothers of babies with birth weight _2500 gm were enrolled as controls. Results: Total 96 mothers were enrolled in this study and 48 mothers in each group. All the information was recorded in a pretested questionnaire. Statistical analysis was done by SPSS. Primipara mother had 3.153 times more likely to deliver LBW baby. Patients having anemia had 3.316 times more likely to deliver LBW baby. Patients having hypertension had 4.120 times more likely to deliver LBW baby. Preterm delivery had 28.927 times more likely to deliver LBW baby. Primipara, anemia, hypertension and preterm delivery were significantly associated with LBW. In multivariate analysis, preterm had 20.619 times more likely to deliver LBW. Conclusion: Primipara, anemia, hypertension and preterm delivery were significantly associated with LBW. Medicine Today 2022 Vol.34(2): 106-110